2014
DOI: 10.1108/jmhtep-05-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Dentistry students’ views about mental illness and impact of a targeted seminar on knowledge and attitudes: a mixed-method study

Abstract: Purpose – The purpose of this paper is to inform education of non-mental health professionals who provide care to people with severe mental illness; to describe dentistry students’ knowledge and views about mental illness, including willingness to engage in various social situations with a person hospitalised for mental illness; and to assess and understand the impact of a targeted lecture on views and attitudes. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…8 Another study exploring dentistry students's views about mental illness and impact of a targeted seminar on knowledge and attitudes found that they understood mental disorder broadly, employing diverse causal models and the attitudes were benevolent and most students reported willingness to provide dental care to affected individuals. 9 Higher benevolence scores among participants indicated that most of them would express kindness and altruism toward the person suffering from any form of mental illness. 10 The participants showed less stereotyping attitude toward mentally ill as they rated low to the statements in stereotyping domain, indicating stereotypes about mental illness like influence of evil spirits, religious afflictions and deviation from societal norms were not considered by most of them.…”
Section: Discussionmentioning
confidence: 98%
“…8 Another study exploring dentistry students's views about mental illness and impact of a targeted seminar on knowledge and attitudes found that they understood mental disorder broadly, employing diverse causal models and the attitudes were benevolent and most students reported willingness to provide dental care to affected individuals. 9 Higher benevolence scores among participants indicated that most of them would express kindness and altruism toward the person suffering from any form of mental illness. 10 The participants showed less stereotyping attitude toward mentally ill as they rated low to the statements in stereotyping domain, indicating stereotypes about mental illness like influence of evil spirits, religious afflictions and deviation from societal norms were not considered by most of them.…”
Section: Discussionmentioning
confidence: 98%
“…As indicated, the nature and purpose of the course was explained to the students at the outset, including that the course was not “self-help” in nature, but aimed at preparing students for their professional work (DeFrank, 2012). Although students in health-related disciplines likely receive some exposure or even formal instruction related to mental health (Attoe et al , 2019; McAllister et al , 2014; O’Reilly et al , 2011; Patterson and Ford, 2014; Stacey and Rayner, 2008; Wheeler et al , 2014), coverage of such topics in business and management programmes is typically scant or absent (Martin et al , 2015; Samra, 2017). Therefore, business students might not anticipate open discussion of mental health within business curricula or courses, and might find some of the material surprising, anxiety producing, uncomfortable or otherwise difficult.…”
Section: Course Context Structure Content and Teaching Methodsmentioning
confidence: 99%
“…Despite these promising findings, there has been a dearth of attention to whether proactively training business administration students as prospective business leaders is associated with positive outcomes. Although mental health training for students in various disciplines has shown encouraging results (Patterson and Ford, 2014; Morrissey et al , 2017; Saunder, 2016), mental health courses and even mental health-related content are typically absent in business curricula (Martin et al , 2015; Samra, 2017). Yet, business and management are disciplinary programmes into which such courses or modules should be embedded (Martin et al , 2015; Samra, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise instructors, such as personal trainers and exercise physiologists, may need to be upskilled to confidently work with adults with mental illness 404 . Such training could include education to increase mental health literacy, reduce stigma, and advice on how to consult with clients about how their mental illness affects their preferences and barriers to exercise 405 .…”
Section: Preferred Source Of Supportmentioning
confidence: 99%